Quantitative MRI Changes During Weekly Ultra-Hypofractionated Prostate Cancer Radiotherapy With Integrated Boost - van Schie, Marcel A.; van Houdt, Petra J.; Ghobadi, Ghazaleh; Pos, Floris J.; Walraven, Iris; de Boer, Hans C. J.; van den Berg, Cornelis A. T.; Smeenk, Robert Jan; Kerkmeijer, Linda G. W.; van der Heide, Uulke A. (Frontiers in Oncology, 2019)
Purpose: Quantitative MRI reflects tissue characteristics. As possible changes during radiotherapy may lead to treatment adaptation based on response, we here assessed if such changes during treatment can be detected. Methods and Materials: In the hypoFLAME trial patients received ultra-hypofractionated prostate radiotherapy with an integrated boost to the tumor in 5 weekly fractions. We analyzed T2 and ADC maps of 47 patients that were acquired in MRI exams prior to and during radiotherapy, and performed rigid registrations based on the prostate contour on anatomical T2-weighted images. We analyzed median T2 and ADC values in 3 regions of interest (ROIs): the central gland (CG), peripheral zone (PZ) and tumor. We analyzed T2 and ADC changes during treatment and compared patients with and without hormonal therapy. We tested changes during treatment for statistical significance with Wilcoxon signed rank tests. Using confidence intervals as recommended from test-retest measurements, we identified persistent T2 and ADC changes during treatment. Results: In the CG, median T2 and ADC values significantly decreased 12% and 8% respectively in patients that received hormonal therapy, while in the PZ these values decreased 17% and 18%. In the tumor no statistically significant change was observed. In patients that did not receive hormonal therapy, median ADC values in the tumor increased with 20%, while in the CG and PZ no changes were observed. Persistent T2 changes in the tumor were found in 2 out of 24 patients, while none of the 47 patients had persistent ADC changes. Conclusions: Weekly quantitative MRI could identify statistically significant ADC changes in the tumor in patients without hormonal therapy. On a patient level few persistent T2 changes in the tumor were observed. Long-term follow-up is required to relate the persistentT2 and ADC changes to outcome and evaluate the applicability of quantitative MRI for response based treatment adaptation.